PERSUSUAN (AR-RADHAA’) MENJADIKAN KEMAHRAMAN DALAM PERKAWINAN (KAJIAN TAFSIR MAUDU’I ALQURAN SURAT AN-NISA AYAT 23) - Thoat Setiawan (JURIS (Jurnal Ilmiah Syariah), 2017)
The implementation of marriage in Indonesia has been equipped with regulations regarding the legal requirements of marriage. One of them is the regulation concerening with whether marriage is permitted by a couple of sepersusuan (a couple who belongs to the same breast feeder) since thetre still marriages that are performed by such couples. This study therefore aimed to figure out the status and posistion of marriage a couple of sepersusuan. The problem of the research in this study was formulated in the following question: what is the status and position regarding with the legal consequences of marriage by sepersusuan couples in the framework of Islamic law.The research method used was Tafsir Maudhu’i  Discussion by collecting and systematically compiling the verses and trying to summarize the interpretations of the commentators (interpreters) on the verses of the Qur'an associated with the theme of sepersusuan (ar-Radhaa ') Making it Permitted In Marriage. After that it was described by observing the Munasabah and Asbabun Nuzul of the verses by referring to some of Tafsir al-Munir's primary sources, Tafsir al-Misbah, Tafsir Ibn Katsir.